KOMUNIKASI POLITIK PASANGAN INDEPENDEN HERMAN NAZAR- DEFI WARMAN PADA PEMILIHAN WALIKOTA PEKANBARU PERIODE 2017-2022 - Saraswati "; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The presence of independent partner is a new thing in local election (pemilukada) of Pekanbaru city. For the first time in history of local election (pemilukada) in Pekanbaru city a parter from independent candidate has passed and can fill all of the requirements for the election. This research aims to know the strategy of Politic Communication and the used of media campaigns by independent partner In Pekanbaru Mayor Election Period 2017 – 2022.This research used descriptive qualitative method. The research subject involved independent partner Herman Nazar – Defi Warman, the leader of winning team, vice secretary and inhabitants. The technique of collecting data used interview, observation, and documentation.The result from this research showed that strategy of politic communication used by the independent partner, Herman Nazar – Defi Warman, if we see from SWOT analysis is have the power from social capital and economic capital. They also have a weakness in having network and strong basic massa. Using the opportunities by getting support from copy of id card which given by the inhabitants. The treaths are coming from incumbent partner and less participation from the inhabitants in the election. The Independent partner , Herman Nazar – Defi Warman used face to face media by joining the direct campaign with the inhabitants. They also used social media such as facebook and youtube to post all of their activities during the campaign . The outside media were also used , such as street banner and billboard that put in strategic places. And also small format like booklet, brochure, poster, stciker, calender and pin which given away to the inhabitants.Keyword: Independent Candidate, Local Election, Political Communication